Amazonella Fouquet et al., 2012 (Anura:Bufonidae) junior homonym of Amazonella Lundblad, 1931 (Acari:Unionicolidae): proposed replacement by Amazophrynella nom. nov. - Fouquet, Antoine; Recoder, Renato; Teixeira, Mauro; Cassimiro, José; Amaro, Renata Cecília; Camacho, Agustín; Damasceno, Roberta; Carnaval, Ana Carolina; Moritz, Craig; Rodrigues, Miguel Trefaut (Zootaxa, 2012)
The genus Amazonella Lundblad, 1931 was originally described for an Amazonian species of water mite (Lundblad 1931: 63). Unaware its existence, Fouquet et al. (2012) re-delimited Dendrophryniscus Jiménes de la Espada, 1870 a genus of small Neotropical toads on the basis of molecular and morphological data, and proposed Amazonella as the name for a clade comprising the Amazonian species (Fouquet et al. 2012: 832). Amazonella Fouquet et al., 2012 is therefore a junior homonym of Amazonella Lundblad, 1931.